ANALYSIS OF THE INFLUENCE OF EMPLOYEE TRAINING AND PROMOTION ON THE WORK PRODUCTIVITY OF PT KEPI BEKASI - Waluyo, Sri (Entrepreneurship Undergraduate Program at Amkop Business School, 2025)
Analysis of the Influence of Employee Training and Promotion on Work Productivity of PT Kawashima Engineering Plastic Indonesia (PT KEPI). This study was conducted to find out whether there is an influence and relationship between Training (X1) and Employee Promotion (X2) together on Work Productivity (Y). This research was conducted at PT Kawashima Engineering Plastic Indonesia (PT KEPI). This research is a quantitative research, and primary data is used as research data. Primary data in the form of answers/questionnaires were distributed to 30 respondents who were employees of PT KEPI. The data analysis method uses Simple Regression Coefficient Analysis, Multiple Regression Coefficient Analysis, Simple Correlation Coefficient Analysis, Multiple Correlation Coefficient Analysis, Determination Coefficient Analysis, Hypothesis T Test, Hypothesis F Test and Descriptive Analysis and using the help of SPSS application version 17.The results of multiple linear regression analysis obtained an equal value of Y = 29.192 – 0.28X1 + 0.94X2, so Training (X1) and Employee Promotion (X2) together have a strong positive influence on Work Productivity (Y) at PT KEPI. If policies are not carried out on Training (X1=0) and Employee Promotion (X2=0), then the Work Productivity (Y) achieved is 29,192. Furthermore, if Job Training is carried out by 1 (X1=1), and Employee Promotion by 1 (X2=1), then Work Productivity (Y) will decrease by 0.28 from X1 and increase by 0.94 from X2. The final result of Work Productivity will increase by 0.66, which is Y = 29.85.Keywords: Training, Promotion, Work Productivity